ANALISIS PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN ISAK 335 PADA MASJID RIYADHUS SHALIHIN KEL. LALOEHA, KEC. KOLAKA, KAB. KOLAKA - Jumriani, Jumriani; Turi, La Ode; Ilham, Surianto (Jurnal Akuntansi Kompetif, 2025)
This study examines the challenges and opportunities in implementing ISAK No. 335 at the Riyadhus Shalihin Mosque in Kolaka. Using a qualitative descriptive approach, data were collected from the mosque's financial records and its management. Findings indicate that ISAK 335 has not been applied due to limited training, low understanding of accounting standards, lack of technology, and minimal external stakeholder support. Financial reports remain informal and non-compliant with ISAK 335. The absence of audits and low awareness of transparency further hinder adoption. Without external support through training, technical aid, and accountability demands, implementation of ISAK 335 is unlikely in the near future. Keywords: Financial statements, ISAK 335, Riyadhus Shalihin Mosque